New developments in optimizing bronchodilator treatment of COPD: a focus on glycopyrrolate/formoterol combination formulated by co-suspension delivery technology - D'Urzo AD; Cazzola M; Hanania NA; Buhl R; Maleki-Yazdi MR (International Journal of COPD, 2018)
Anthony D D’Urzo,1 Mario Cazzola,2 Nicola A Hanania,3 Roland Buhl,4 M Reza Maleki-Yazdi5 1Department of Family and Community Medicine, Faculty of Medicine, University of Toronto, Toronto, ON, Canada; 2Department of Experimental Medicine and Surgery, Tor Vergata University of Rome, Rome, Italy; 3Section of Pulmonary and Critical Care Medicine, Baylor College of Medicine, Houston, TX, USA; 4Pulmonary Department, Mainz University Hospital, Mainz, Germany; 5Division of Respiratory Medicine, Women’s College Hospital, University of Toronto, Toronto, ON, Canada Abstract: COPD causes considerable health and economic burden worldwide, with incidence of the disease expected to continue to rise. Inhaled bronchodilators, such as long-acting muscarinic antagonists (LAMAs) and long-acting β2-agonists (LABAs), are central to the maintenance treatment of patients with COPD. Clinical studies have demonstrated that combined LAMA + LABA therapies improve efficacy while retaining a safety profile similar to LAMA or LABA alone. This has led to the development of several LAMA/LABA fixed-dose combination (FDC) therapies, which provide patients with the convenience of two active compounds in a single inhaler. GFF MDI (Bevespi Aerosphere®) is an FDC of glycopyrrolate/formoterol fumarate 18/9.6 µg formulated using innovative co-suspension delivery technology for administration via metered dose inhaler (MDI). GFF MDI was developed to make a treatment option available for patients who have a requirement or preference to use an MDI, rather than a dry powder or soft mist inhaler. Now that several LAMA/LABA FDCs have been approved for use in COPD, we review the impact of dual-bronchodilator treatment on COPD therapy and discuss recent clinical studies that are helping to develop a more comprehensive understanding of how LAMA/LABA FDCs can improve patient outcomes. Keywords: long-acting bronchodilator, LAMA, LABA, chronic obstructive pulmonary disease, fixed-dose combination, GFF MDI